THERAPEUTIC MODALITIES AND COURSE OD THE DISEASE IN PATIENTS WITH AUTOIMUNE PEMPHIGUS (AP) TREATED AT THE CLINIC OF DERMATOVENEROLOGY IN THE PERIOD 2013-2018. - Madžgalj, Šućro (Medicinski podmladak, 2021)
Introduction: Autoimmune pemphigus (AP) is one of the most severe dermatologic diseases. AP belongs to the group of organ-specific autoimmune disorders, with autoantibodies directed against cell- surface antigens on keratinocytes, mostly desmogleins. Three main types of AP have been described, depending on the patients' clinical and histologic features and the different target antigens: Pemphigus vulgaris (PV), Pemphigus foliaceus (PF), each with its own subtypes and paraneoplastic pemphigus (PNP). The clinical course and prognosis of AP depend on its subtype, therapeutic modalities and their side effects. The main goal of treatment is to achieve and maintain remission without any systemic therapy or with minimal therapeutic doses (“maintenance therapy”).The aim: A retrospective study of hospitalized patients with various forms of AP, analysis of clinical course and evaluation of therapeutic modalities employed.Material and methods: A total of 158 inpatients with diagnosed AP, admitted to the Clinic of Dermatovenereology, Clinical Centre of Serbia, from 2013 to 2018, with a subsequent follow-up of 6 to 12 months, were included in this study. Demographic and clinical data as well as treatment approaches were analyzed using descriptive and analytic statistics.Results: The most common subtype encountered was PV (72.15%); in the largest number of patients (46.84%) the disease occurred between ages 39-59. Conventional corticosteroid treatment was most frequently used (67.41%), along with azathioprine (66.86%) as the most common immunosupressive drug. In 60.8% of patients no side effects or disease complications were recorded. During the follow-up, at the end of 2018, 48.1% of patients achieved remissionConclusion: We have shown a high incidence of PV. Treatment approaches used in our patients were in accordance with the pemphigus subtype and course of the disease. A significant number of patients achieved clinical remission.
Keywords: Keywords: pemphigus, therapeutic modality, clinical course, side effects